Analisis 1 Timotius 2:11-12 terkait Perdebatan Kepemimpinan Wanita dalam Gereja - Stella, Yunita (Jurnal Teologi dan Pelayanan Kerusso, 2024)
One of the most controversial texts in the history of biblical interpretation relating to women's participation in church teaching and leadership is 1 Timothy 2:11-12. This text is seen as completely inconsistent with the total testimony of the NT. The Complementarian group used this text as the basis for prohibiting women from teaching and leading in the church. Meanwhile, the Egalitarian group believes that Paul's statement in 1 Timothy 2:11-12 is not a manual for church order that must be applied universally to limit women's ministry in all times and places. This research analyzes the text of 1 Timothy 2:11-12 regarding the debate on women's leadership in the church. The method used is exegesis, with the aim of finding meaning according to the original author's intentions when the text was written. The results of this research found that there are certain women who have exercised authority with dominance that demeans men. For that reason, Paul instructed certain women not to teach and command men.